Correlation of urinary mitochondrial DNA with clinical profiles and prognostic effects in primary membranous nephropathy - Hou-hui Jiang; Yan-qin Fan; Zhong-ping Wei; Ding-ping Yang; Guo-hua Ding (Linchuang shenzangbing zazhi)
Objective To explore the correlation between urinary mitochondrial DNA（mtDNA） and the severity and prognosis of primary membranous nephropathy（PMN）.MethodsA total of 56 patients were definitely diagnosed as PMN through renal biopsy from May 2022 to June 2023. Clinical and laboratory data were recorded. Morning mid-stream urine samples were collected for detecting the copy numbers of cytochrome-c oxidase-3（COX3） and NADH dehydrogenase subunit-1（ND1） genes in mtDNA. The correlation between baseline mtDNA copy number and nephrotic syndrome（NS） was examined through univariate and multivariate Logistic regression models. During follow-ups, Kaplan-Meier survival curves were plotted for analyzing the differential remission outcomes between high and low urinary mtDNA copy number groups.Results COX3 and ND1 copy numbers spiked in medium-risk group[COX3 = 5.532（5.318, 5.797）, ND1 = 5.575（5.270, 5.815）] and high-risk group [COX3 = 5.575（5.270, 5.815）, ND1 = 5.575（5.270, 5.815）] as compared with low-risk group[COX3 = 5.362（5.194, 5.508）, ND1 = 5.386（5.272, 5.528）]（P＜0.05）.COX3 and ND1 copy numbers were correlated positively with 24-hour urinary protein（P = 0.031, P = 0.041） and negatively with albumin（P = 0.032, P = 0.005）. The predictive value of COX3 and ND1 copy numbers in PMN with NS was examined with receiver operating characteristic（ROC） curve. And grouping was based upon optimal cutoff values of COX3 and ND1 copy numbers. The results indicated that the risk of nephrotic syndrome（NS） was higher in group with elevated COX3 and ND1 copy numbers versus group with lower copy numbers（Model 1: OR = 3.51, P = 0.019; OR = 2.89, P = 0.024）. After adjusting for age, gender, systolic blood pressure, diastolic blood pressure, anti-PLA2R antibodies and eGFR, the risk of NS remains higher in group with elevated COX3 and ND1 copy numbers（Model 3: OR = 2.65, P = 0.031; OR = 2.17, P = 0.029）. In terms of disease remission, Kaplan-Meier survival curve analysis revealed no significant correlation between COX3 and ND1 copy numbers and remission outcomes of PMN（log-rank test P = 0.630, P = 0.208）.ConclusionUrinary mtDNA is significantly higher in PMN patients of medium/high-risk group than those of low-risk group. Urinary mtDNA is associated with an elevated risk of NS in PMN patients, However, its predictive effect on disease remission requires further studies.